Validation of a New Hyperviscoelastic Model for Deformable Polymers Used for Joints between RC Frames and Masonry Infills - Arkadiusz KWIECIEŃ; Matija GAMS; Theodoros ROUSAKIS; Alberto VISKOVIC; Jože KORELC (Engineering Transactions, 2017)
In the paper, an attempt to alleviate the problem of premature damage to infills by using flexible polymers between the infill and the r.c. frame is presented. The flexibility of the polymer could serve to reduce the stress concentrations and thereby reduce damage to infills on one hand, and provide a high amount of damping and ductility on the other. Its efficiency is tested by cyclic shear tests carried out on a large-scale model. In the numerical part, the material is modelled using for the purpose developed finite element. The finite element with the new hyperviscoelastic constitutive model was coded in the AceGen/AceFEM program.